Occurrence and damage of the alfalfa root longhorn beetle (Plagionotus floralis Pallas, 1773) in old alfalfa stands in Hungary - Bozsik, András (Acta Agraria Debreceniensis, 2010)
The alfalfa root longhorn beetle is a pest of small importance in old alfalfa stands. It is rarely cited in the international, national literature, or even mentioned in specialized manuels. Plagionotus floralis is common in Hungary but its population density is low. It is a polyphagous species but it has importance - regarding the references – only in alfalfa. This paper analyses data gained in old alfalfa fields at two different regions of the country (Máriabesnyő, Debrecen). Damage of P. floralis was 56% in the roots of an 8-year-old stand in Máriabesnyő. Lenghts of tunnels were between 3 and 22 cm. In spite of the tunnels the alfalfa plants were viable. There was no root longhorn beetle in the 15-year-old Debrecen stand, however it has been found former in the region. The reason for the important density of P. floralis in Máriabesnyő could be the considerable diversity and covering of flowering weeds around the field. Adults of P. floralis feed on flower pollen and nectar. As to the Debrecen area,weeds were cut regularly, so the edge vegetation was poor. Present conditions (no pest control on alfalfa fields, overuse of old and failing alfalfa stands, many untrained growers) favour the reproduction and possible damage of alfalfa root longhorn beetle.